Preservation of molecular fossils in carbonate concretions in cretaceous shales in the songliao basin, northeast China - Lin, Lamei; Cheng, Fuqi; Xu, Jinjun (Frontiers in Earth Science, 2023)
Paleoenvironmental information is better preserved in carbonate concretions. In this study, carbonate concretions in the Cretaceous Nenjiang shale, Songliao Basin, were examined to determine whether molecular fossils reflective of the paleoenvironment were better preserved at these sites. Organic and inorganic geochemical characteristics of the concretions and surrounding rocks were analyzed using a series of techniques, including SEM, LA-ICP-MS, GC-MS-MS, and GC-IRMS. The concretions are composed of high content microcrystalline dolomite. The δ13Ccarb and δ18Ocarb values of the concretionary dolomite were significantly higher than those of the surrounding rocks. The dolomite show enrichment in the LREEs and have a negative Eu anomaly. The concretion biomarkers showed distribution characteristics similar to those of surrounding rocks. This suggested that the molecular fossils preserved in concretions were mainly inherited from surrounding rocks. However, the concretions contained more C27 sterane and hopanes, with the hopane/sterane ratio being significantly higher than that of surrounding rocks (1.49 v. 0.86). Moreover, the relative content of 2-methylhopane was 2.4–6.6 times that of the surrounding rocks. This indicated changes in the biological equilibrium of source organisms within and outside the concretions. It was possible that the unstable organic matter at the core increased the bacterial concentration and activity inside the concretions. Both the hydrogen index and biomarker-derived indicators implied that the transformation of organic matter in concretions was minimized when compared with their host rock. The isotope δ13C16-30 was 1‰–3‰ more prevalent in individual N-alkane hydrocarbons in the concretions than in surrounding rocks, likely owing to differences in lithology, bacterial action, and degree of weathering. The study concluded that carbonate concretions could preserve molecular fossils better than the surrounding rocks, and the in-depth organic geochemical analysis of concretions could provide a valuable reference for research into early life forms.